Pemodelan Faktor Risiko Penyakit Tuberkulosis di Kota Lhokseumawe - Novianti Novianti; Roslinawati; Siska Desta Roza; Yeffi Masnarivan (HEALTH CARE : JURNAL KESEHATAN, 2021)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Tuberculosis is a health problem that until now has become the most infectious and very deadly disease in the world. TB cases in Aceh Province in 2018 were found to be 8,471 cases. The city of Lhokseumawe with the highest CNR of tuberculosis cases in Aceh Province was 351 per 100,000 population. The purpose of this study was to determine the model of risk factors that influence tuberculosis in Lhokseumawe City. This research is a descriptive study using secondary data analysis. This research was conducted in Lhokseumawe City in March - September 2021. This study used secondary data from the Lhokseumawe City BPS and Lhokseumawe City Health Office 2019. The results showed that the highest TB prevalence rate was in banda sakti sub-district at 336 per 100,000 population. Meanwhile, the sub-district with the lowest TB prevalence rate is in Muara Dua District, which is 201 per 100,000 population. There are 2 variables that significantly differentiate between the two clusters, namely the proportion of households with a ground floor and population density. The population density variable is the most dominant variable causing TB disease in Lhokseumawe City.